Decreased serum apolipoprotein AII/AI ratio in systemic amyloidosis. Issue 4 (1st April 1998) - Yamada, Toshiyuki; Ozawa, Tetsuo; Gejyo, Fumitake; Okuda, Yasuaki; Takasugi, Kiyoshi; Hotta, Osamu; Itoh, Yoshihisa
Abstract : OBJECTIVE: To investigate if serum apolipoprotein A-I and A-II (apoAI and apoAII) concentrations change in subjects with systemic amyloidosis secondary to underlying disorders. METHODS: Serum concentrations of apoAI and apoAII were measured in 21 multiple myeloma patients, including eight with amyloidosis; 95 rheumatoid arthritis patients, including 45 with amyloidosis; and 73 haemodialysis patients, including 32 with amyloidosis. RESULTS: ApoAII values tended to be reduced in subjects with amyloidosis in each group, but could not effectively distinguish amyloidosis. However, apoAII/AI ratios were significantly lower in subjects with amyloidosis in all groups. The ratio of 0.2 had diagnostic sensitivity and specificity for amyloidosis; 50% and 100%, respectively, in multiple myeloma; 80% and 78%, respectively, in rheumatoid arthritis; and 46% and 90%, respectively, in patients requiring long term haemodialysis. CONCLUSION: The apoAII/AI ratio can be a useful biochemical marker of suspect amyloidosis in patients with underlying diseases, especially those with rheumatoid arthritis.